Sintering Mechanisms of Convention Nanodensification and Field Assisted Processes - Castro, Ricardo.; Castro, Ricardo.; van Benthem, Klaus.; van Benthem, Klaus. (Engineering Materials,, 2013)
Sintering process studies have re-emerged strongly in the past decade due to extensive discussions about the stabilization of nanoparticles and nanostructures, and the development of controlled nanograined bulk materials. This book presents the state-of-art in experiments and theory of assisted sintering, nanosintering and grain growth. The scope ranges from powder metallurgy to ceramic and composites processing. The challenges of conventional and novel sintering and grain growth in nanopowders and nanostructures are addressed, being useful for students as well as professionals interested in sintering at the nanoscale.